2022
DOI: 10.1155/2022/4009354
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis and Validation of Solute Carrier Family 25 (SLC25) and Its Correlation with Immune Infiltration in Pan-Cancer

Abstract: As the largest gene family functioning in protein transport among human solute carriers, the SLC25 family (mitochondrial carrier family) can participate in development of cancer. However, a comprehensive exploration for the exactly roles of SLC family remains lacking. In the present study, a total of 15 functional SLC25 family genes were retrieved from all current publications. And multidimensional analyses were systematically performed based on the transcriptome and genome data of SLC25 family from a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…According to a recent study, tumor-associated macrophages (TAMs) may regulate the heme oxygenase (HO-1) expression level by controlling SLC25A4, promoting M2 macrophage polarization, and enhancing tumor metastasis. Meantime, particular flaws in SLC25A4 trigger the activation of hypoxia-inducible factor (HIF-1α) within inflammatory macrophages, consequently fostering heightened lactate dehydrogenase (LDH) expression levels and concurrent elevation in glycolysis 45 , 46 . Furthermore, studies have demonstrated the crucial role of regulatory T cells, natural killer cells, and dendritic cells in RA progression 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, tumor-associated macrophages (TAMs) may regulate the heme oxygenase (HO-1) expression level by controlling SLC25A4, promoting M2 macrophage polarization, and enhancing tumor metastasis. Meantime, particular flaws in SLC25A4 trigger the activation of hypoxia-inducible factor (HIF-1α) within inflammatory macrophages, consequently fostering heightened lactate dehydrogenase (LDH) expression levels and concurrent elevation in glycolysis 45 , 46 . Furthermore, studies have demonstrated the crucial role of regulatory T cells, natural killer cells, and dendritic cells in RA progression 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The physiological role of TPP1 is to recruit telomerase to chromosome ends and protect the ends from the ligations of unwanted material 32,33 . SLC25A4 is reportedly downregulated in gastric adenocarcinoma, colon adenocarcinoma, and renal cell carcinoma, compared with normal cells, and may, therefore, be used as a prognostic factor in renal cell carcinoma 34,35 . POMP promotes the assembly of 20S proteasome, leading to tumor suppressor gene p53 and retinoblastoma (Rb) through the ubiquitin-independent proteolysis, which promotes the occurrence of colorectal or rectal adenocarcinoma and multiple myeloma 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Among other genes in the present OTA‐specific “mitochondrion” gene cluster, solute carrier (SLC)25A23, encoded by Slc25a23 , is a calcium‐dependent mitochondrial solute carrier involved in calcium uptake into mitochondria (Bassi et al, 2005). Multidimensional analyses systematically performed on the expression status (tissue mRNA, protein, and cell lines) of the SLC25 family from a pan‐cancer perspective based on a variety of online databases in human cancers revealed that SLC25 is one of the family members involved in the immune microenvironment of cancer (Liu et al, 2022). Among the SLC25 family of proteins, SLC25A7 is highly expressed in gastric adenocarcinoma and colon adenocarcinoma, whereas SLC25A23 is reported to be downregulated in colon adenocarcinoma (Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Multidimensional analyses systematically performed on the expression status (tissue mRNA, protein, and cell lines) of the SLC25 family from a pan-cancer perspective based on a variety of online databases in human cancers revealed that SLC25 is one of the family members involved in the immune microenvironment of cancer (Liu et al, 2022). Among the SLC25 family of proteins, SLC25A7 is highly expressed in gastric adenocarcinoma and colon adenocarcinoma, whereas SLC25A23 is reported to be downregulated in colon adenocarcinoma (Liu et al, 2022). Furthermore, epigenetic downregulation of SLC25A23 has been observed in glioblastomas, and its low expression was associated with a poorer prognosis of glioblastomas (Sharma et al, 2017).…”
Section: Functional Data Analysismentioning
confidence: 99%